The Future of Libraries: Utilizing Artificial Intelligence and Big Data in Libraries - Yılmaz, Malik (Information World, 2025)
Artificial intelligence and big data analytics are creating transformative impacts not only in the field of technology but also across various domains such as education, healthcare, public administration, and information services in the knowledge-driven world of the 21st century. The book titled The Future of Libraries: The Use of Artificial Intelligence and Big Data in Libraries, authored by Burak Savaş Sarıçoban, is a comprehensive study that examines the implications of this technological transformation within the context of libraries, addressing both theoretical and practical dimensions. Based on the author’s master’s thesis, the work explores the effects of artificial intelligence and big data analytics on libraries and posits that artificial intelligence is among the most influential technologies in the process of digital transformation. The book discusses in detail how libraries can navigate this transformation process, drawing on literature reviews, field research, and international case studies, thereby offering an original contribution to the field.